HUBUNGAN KARAKTERISTIK INDIVIDU, KEBERADAAN PMO DAN EFEK SAMPING OBAT DENGAN KEPATUHAN MINUM ARV DI KLINIK VCT RSUD DR. M YUNUS KOTA BENGKULU TAHUN 2017 - Rama Dhania Ramadhania; Sori Muda Sarumpaet; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT   The number of people living with HIV in ARV therapy at VCT clinic RSUD Dr. M Yunus Kota Bengkulu from 2014 until 2016 increased, from 86 peoples to 129 peoples. One way to overcome HIV / AIDS is to take antiretroviral drugs (ARV). Use of long-term antiretroviral drugs requiring high adherence to achieve success and prevent drug resistance. This research then comes to find the relationship of individual characteristics, the presence of drug supervisor, and drug side effects with ARV drug adherence in people living with HIV in VCT clinic RSUD Dr. M Yunus Bengkulu city on 2017. This research was done with cross sectional design with 90 samples of ODHA who underwent ARV therapy obtained by consecutive sampling technique. Data using questionnaire and analyzed by chi square test. The result of univariate analysis showed that people living with HIV in VCT clinic RSUD Dr. M. Yunus Bengkulu City on 2017 at the most ≥ 34 years old (52.2%), male (55.6%), mild educated (72.2%), married (46,8%), long-term antiretroviral ≥1 years (75.6%), using the first line ARV regimens (94.4%), had drug supervisor (74.4%), did not feel any more drug side effects (76.7%) and had mild adverse events (66.7%). The proportion of ARV adherence was 76.7% and not adherence was 23.3%. Based on bivariate test result showed that highly educated patients were more adherence than low-educated patients (p = 0.010) and long-term ARV therapy ≥1 years were more adherent than patients who had long-term ARV therapy <1 year (p = 0.011) Keywords: HIV / AIDS, ARV, Adherence